REFLECTING ON PEDAGOGY: TEACHING AND LEARNING IN AN ARMENIAN UNDERGRADUATE CLASSROOM (EDUCATION IN THE 21ST CENTURY, 2025)
This article constitutes the first part of a two-part study and focuses on the author’s teaching experience with first-year students of the “Social Pedagogy” bachelor’s program at a state university in Armenia. The article is presented as a personal academic reflection with an emphasis on the teaching process itself. Although much of the discussion is based on personal experience, the observations and analyses offered here may be applicable and valuable in similar pedagogical contexts. The article first outlines the pedagogical approaches initially intended versus those actually implemented, followed by an analysis of student responses, taking into consideration both local and global pedagogical challenges that emerged during classroom interactions. In the subsequent discussion, the difficulties arising between traditional and alternative pedagogical methods are examined, highlighting their relevance within the Armenian context against the backdrop of a worldwide shift toward cognitivist and student-centered approaches. The article concludes with several suggested guidelines for modifications aimed at improving the effectiveness of future course delivery.
Keywords: cooperative pedagogy; pedagogical process; alternative teaching methods; traditional methods; pedagogical challenges; educational environment